Menguji Peran Brand Image: Green Marketing dan Corporate Social Responsibility dalam Keputusan Pembelian Produk Perusahaan Multinasional - Zusrony, Edwin; Kusumaningtyas, Dhevi Dadi; Manalu, Gibson; Sulistyowati, Pemilia; Madyoningrum, Asri Winanti (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The research aims to examine the role of brand image: green marketing and corporate social responsibility in purchasing decisions for multinational companies in the F&B sector. The population is consumers of F&B products from multinational companies in the city of Semarang with a sample of 100 respondents taken using a purposive sampling technique. The data collection technique uses a questionnaire with Likert scale parameters of points one to five points. The data analysis technique uses the SEM-PLS method and is processed using SmartPLS 4.0.9.9 software. research results found that green marketing has a positive and significant effect on purchasing decisions, green marketing has a positive and significant effect on brand image, corporate social responsibility has a positive and significant effect on purchasing decisions, corporate social responsibility has a positive and significant effect on brand image and brand image has a positive effect and significant to purchasing decisions. By carrying out mediation tests, it was concluded that brand image was significant as a mediator of the relationship between green marketing and corporate social responsibility on purchasing decisions.